Toxoplasma gondii infection and the risk of adult glioma in two prospective studies. Issue 10 (11th January 2021) - Hodge, James M.; Coghill, Anna E.; Kim, Youngchul; Bender, Noemi; Smith‐Warner, Stephanie A.; Gapstur, Susan; Teras, Lauren R.; Grimsrud, Tom K.; Waterboer, Tim; Egan, Kathleen M.
Abstract: Toxoplasma gondii ( T gondii ) is a common parasite that shows affinity to neural tissue and may lead to the formation of cysts in the brain. Previous epidemiologic studies have suggested an association between glioma and increased prevalence of T gondii infection, but prospective studies are lacking. Therefore, we examined the association between prediagnostic T gondii antibodies and risk of glioma in two prospective cohorts using a nested case‐control study design. Cases and matched controls were selected from the American Cancer Society's Cancer Prevention Study‐II Nutrition Cohort (CPSII‐NC) (n = 37 cases and 74 controls) and the Norwegian Cancer Registry's Janus Serum Bank (Janus) (n = 323 cases and 323 controls). Blood samples collected prior to diagnosis were analyzed for antibodies to two T gondii surface antigens (p22 and sag‐1), with individuals considered seropositive if antibodies to either antigen were detected. Conditional logistic regression was used to calculate odds ratios (OR) and 95% confidence intervals (95% CI) for each cohort. In both cohorts, a suggestive increase in glioma risk was observed among those infected with T gondii (OR: 2.70; 95% CI: 0.96‐7.62 for CPSII‐NC; OR: 1.32, 95% CI: 0.85‐2.07 for Janus), particularly among participants with high antibody titers specific to the sag‐1 antigen (CPSII‐NC OR: 3.35, 95% CI: 0.99‐11.38; Janus OR: 1.79, 95% CI: 1.02‐3.14). Our findings provide the first prospective evidence of an association between T gondii infection and risk of glioma. Further studies with larger case numbers are needed to confirm a potential etiologic role for T gondii in glioma. Abstract : What's new? The etiology of glioma remains poorly understood, with only a few known non‐modifiable risk factors identified. Previous ecological and case‐control studies have suggested an association between Toxoplasma gondii infection and increased glioma risk. Here, individuals who were seropositive for exposure to antigens from the tachyzoite stage of the parasite life cycle were more likely to be diagnosed with glioma in the 13 years following blood collection. The results provide the first prospective evidence of a potential association between T gondii infection and risk of glioma in adults and suggest that reducing exposure could provide an avenue to modify glioma risk.